Czujne istnienie w doczesności. Raz jeszcze o dominancie poezji Bolesława Leśmiana - Łukaszuk, Małgorzata (Colloquia Litteraria, 2020)
The article concerns a significant problem in the reflection on the work of B. Leśmian. About his poetic ontology have been writing, among others, M. Głowiński, J. Trznadel, Z. Łapiński. The author organizes research perspectives. Proposing a careful reading of the works, she recognizes the „positive ontology” as a dominant of the poetic imagination of Leśmian: a strong being and recognition of the reality of the world.